Determination of Total Saponin Content and Antioxidant Activity Using DPPH (2,2-diphenyl-1-picrylhydrazyl) Method of 70% Ethanol Extract of Sidaguri Leaves (Sida rhombifolia L.) - Wirman, Adia Putra; Kristiana, Helda; Sunaryo, Hadi (Malikussaleh University, Aceh, Indonesia, 2024)
Health is the most important and primary thing in human life. Industry and human lifestyle development have both positive and negative impacts. One of the adverse consequences to be aware of is the proliferation of a variety of degenerative diseases. Sidaguri leaves (Sida rhombifolia L.) grow naturally on roadsides, grasslands, forests, fields, areas exposed to bright sunlight, and slightly sheltered places. It is a plant that is widespread in tropical areas ranging from lowlands to 1,450 m above sea level throughout the world. The plant's chemical content includes alkaloids, hypoparin, flavonoids, triterpenoids, sterols, sugars, vaccissinol, vaccissinone, betaine, and phenylalanineSidaguri leaves (Sida rhombifolia L.) are medicinal plants from the Malvaceae family. Almost all parts of this plant can be used for medicinal purposes, particularly in alternative medicine. This study aimed to determine the total saponin content in a 70% ethanol extract of Sida rhombifolia L. Sidaguri leaves, extracted using the maceration method and a 70% ethanol solvent. Using vanillin, H2SO4, and diosgenin as standards, we used UV-Vis spectrophotometry to find out how much total saponin was present. We measured antioxidant activity using the DPPH free radical scavenging test. The test showed that the 70% Sidaguri ethanol extract had a total saponin content of 196.28 ± 1.60 mg DE/g. It also had an IC50 value of 208.63 ± 7.73 mg/mL against DPPH in the antioxidant activity test. This shows the potential of Sidaguri leaf extract as a natural antioxidant.